PENERAPAN METODE WEIGHTED PRODUCT DALAM PERANKINGAN KINERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN DELI SERDANG - Nurmala Sari; R. Fanry Siahaan (JURNAL MAHAJANA INFORMASI, 2021)
In life, we need a way of making decisions. In computer science, the method used in making a decision can be done with the science of decision support systems. This study uses a Decision system with the Weighted Product Method in ranking the performance of employees at the Department of Population and Civil Registration of Deli Serdang Regency. The place of research in this study was carried out at the Department of Population and Civil Registration of Deli Serdang Regency. This study uses an alternative sample of employee data as many as 10 honorary employee data in the field of Population Registration. The Decision Support System created can assist the Personnel in making decisions. From 10 alternative data obtained from the staffing side, it was found that 3 employees with the lowest rank who would not have their work contact extended, namely Ibnu Rozak Aulia (A10) with a value of 0.087130, Sri Melli Amnar Siregar, SE (A3) with a value of 0.078676, Anhalfi Pangidoan ( A1) with a value of 0.076066. This system is built with web-based and MYSQL as database.